مولانا وحید الدین خان ؒکا نظریہ دعوت :تجزیاتی مطالعہ - Irfan, Muhammad (Mujalla Islami Fikr-o-Tahzeeb (MIFT) / مجلہ اسلامی فکر و تہذیب, 2025)
Dawah has a special room in Maulana Wahid- Dud-Din Khan’s intellectual project and contrary to the Islamic tradition; Maulana believed that only Dawat is the solution to all the problems of Muslim Ummah. Maulana opines that instead of directly targeting various problems, Muslims should focus all their attention on Dawah. By this, Allah will clear the way for the solution of all other problems. Maulana says in the later periods of Muslim history, the main reason for the problem faced by Muslim Ummah was that the dawah mind was lost within them. They began to engage in unrelated activities in the name of "religious struggle" and they engaged in conflict and war. Maulana opines modern man has been seriously disappointed by war ideas and violent experiences. Violent nationalism, the aggressive philosophies of Marxism and Nazism have given him a very bitter reaction. Seeing the lethality of the new weapons, he has become increasingly war-crazed. He is looking for an alternative view that shows the way to the welfare of humanity without war and this view can only be offered by Islam. Modern man is standing at the door of Islam, in such situations, if the process of dawah is done correctly, most of the people will find Islam as the voice of their heart.